2012
DOI: 10.2304/plat.2012.11.3.423
|View full text |Cite
|
Sign up to set email alerts
|

A Cultural Scavenger Hunt: Tools of Engagement

Abstract: The authors describe the use of a cultural scavenger hunt to engage visiting students in cultural conversations within a short-term study-abroad course in the Caribbean. Students from a host university developed questions designed to engage visiting students in dialog with local residents and encouraged the students to return with artifacts and answers to questions. The authors outline how they developed the scavenger hunt, the activities it required of the students, and possible variations for use in other se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 6 publications
2
7
0
Order By: Relevance
“…Similar to prior research utilizing cultural scavenger hunts (Doyle et al, 2004; Wesp & Baumann, 2012), our results are promising. Both studies reported in this article yielded exclusively positive results with different samples and using different measures.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Similar to prior research utilizing cultural scavenger hunts (Doyle et al, 2004; Wesp & Baumann, 2012), our results are promising. Both studies reported in this article yielded exclusively positive results with different samples and using different measures.…”
Section: Discussionsupporting
confidence: 86%
“…Overall, the current findings align with prior research on cultural scavenger hunts (Doyle et al, 2004; Wesp & Baumann, 2012) as an efficient and enjoyable way to encourage students to interact with diverse individuals and immerse themselves in the local culture. As programs look to internationalize their psychology curriculum and introduce high-impact practices (Brownell & Swanner, 2009; Kuh, 2008) like study abroad to their offerings, faculty are encouraged to be mindful of the intentional pedagogy of intercultural competence that should occur for students to fully benefit from their study abroad experience.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations